1999
DOI: 10.1177/000456329903600522
|View full text |Cite
|
Sign up to set email alerts
|

Compound Heterozygous Hereditary Coproporphyria with Fluorescing Teeth

Abstract: In Europe, hereditary coproporphyria (HCP) is the third commonest acute hepatic porphyria after acute intermittent porphyria and variegate porphyria. It is inherited as an autosomal dominant trait and excessive excretion of coproporphyrin (copro) III in faeces is the striking biochemical abnormality.' Its clinical expression, with an increase in urinary (j-aminolaevulinic acid (ALA), porphobilinogen (PBG) and porphyrins, is characterized by neurovisceral and cutaneous symptoms. PATIENTS AND METHODSA IO-year ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Until now, a total of 34 different mutations had been identified in the CPO gene of patients suffering from HCP in heterozygous or homozygous form (Doss et al 1999;Lamoril et al 2001;Petersen et al 2000;Sassa et al 1997; Human Gene Mutation Database). In the present study, DGGE analysis and sequencing identified two novel and two previously reported mutations in five of nine investigated Swedish HCP families.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, a total of 34 different mutations had been identified in the CPO gene of patients suffering from HCP in heterozygous or homozygous form (Doss et al 1999;Lamoril et al 2001;Petersen et al 2000;Sassa et al 1997; Human Gene Mutation Database). In the present study, DGGE analysis and sequencing identified two novel and two previously reported mutations in five of nine investigated Swedish HCP families.…”
Section: Discussionmentioning
confidence: 99%
“…Several HCP-coupled mutations have been identified in the CPO gene (Doss et al 1999;Lamoril et al 2001;Petersen et al 2000;Sassa et al 1997, and Human Gene Mutation Database). The mutations identified so far are, with a few exceptions, restricted to single families, making HCP a genetically heterogeneous disease.…”
Section: Introductionmentioning
confidence: 99%
“…Presentation with skin lesions alone is uncommon among patients with HCP; the few cases reported have usually been associated with hepatobiliary dysfunction (Brodie et al 1977;Hawk et al 1978;Martasek 1998). In contrast, the very rare homozygous form of HCP presents in childhood with skin lesions Martasek et al 1994b;Doss et al 1999). Harderoporphyria is characterized by neonatal hemolytic anemia, sometimes ac-companied by skin lesions and accumulation of harderoporphyrin in feces (Nordmann et al 1983;Lamoril et al 1995;Lamoril et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…CPOX gene mutation analysis revealed that our patient was homozygous for the previously described missense mutation c.980A>G (Doss et al 1999) which predicts the substitution of a highly conserved histidine (Figure 1) by an arginine at amino acid 327 (p.H327R) in the CPOX enzyme subunit. Our proband’s asymptomatic parents and four year old healthy sibling were heterozygous for the mutation, consistent with their having autosomal dominant HCP (typically non-penetrant).…”
Section: Discussionmentioning
confidence: 66%
“…Sequencing of the family’s CPOX gene identified homozygosity for the missense mutation, p.R231W (renumbered p.R331W by Delfau-Larue et al 1994), predicting an arginine to tryptophan substitution (Martasek et al 1994). Doss et al (1999) described a 10 year old girl who had homozygous HCP. She presented with skin fragility, erythema and scarring of hands and feet, and erythrodontia.…”
Section: Introductionmentioning
confidence: 99%